Economic Valuation of Tourist Attractions with Travel Cost Approach - Susilowati, Indah; Musliha, Cici; Al-Hafidz, Zulfikar; Prabowo, Sigit; Sari, Dwi Putri Wulan; Ardana, Raditya (Universitas Warmadewa, 2024)
Umbul Sidomukti is an excellent tourist area with several tourist objects. Umbul Sidomukti tourism was designated as a tourist attraction because the area has a potential economic value from the tourism sector. This study aims to determine the economic value of the Umbul Sidomukti tourist attraction based on the travel cost method (TCM). This study uses the travel cost method based on primary data from in-person interviews and online surveys with 105 visitors visiting the Umbul Sidomukti tourist area. The study results show that the relationship between travel costs and distance and the number of tourist visits has a ceteris paribus negative relationship following tourism demand. Service and income variables have a positive effect that is not significant. Meanwhile, the potential economic value of the Umbul Sidomukti tour is estimated at Rp. 28,142,763,075 per year. This research can be used to develop natural tourism objects using the travel cost approach, especially the Umbul Sidomukti tourism object.